DIPG-50. A NOVEL ORTHOTOPIC PATIENT-DERIVED XENOGRAFT MODEL OF RADIATION-INDUCED GLIOMA. (4th December 2020) - Whitehouse, Jacqueline; Howlett, Meegan; Stanley, Jason; Hii, Hilary; Valvi, Santosh; White, Christine; Mayoh, Chelsea; Wong, Marie; Strowger, Brooke; Dyke, Jason; Cowley, Mark; Gottardo, Nicholas; et al.
Abstract: Diffuse midline glioma (DMG) can arise as a primary tumour but also as a consequence of radiation therapy (RT) in survivors of other paediatric brain tumours. Radiation-associated gliomas are molecularly distinct from primary gliomas and have poorer overall survival. We report a case of radiation-associated DMG following treatment for medulloblastoma, and the development of a matched patient-derived xenograft (PDX) model. A four-year-old boy diagnosed with medulloblastoma was treated with surgical resection, RT and chemotherapy (COG:CCG-99701-Arm B). Eleven years post-diagnosis, the patient relapsed with radiation-associated DMG, participated in a Phase I clinical trial (COG:ACNS0927), and passed away eight months later. Tumour tissue collected at autopsy was intracranially implanted into immunodeficient mice and serially transplanted in vivo . Immunohistochemistry demonstrated both the primary DMG and PDXs expressed PDGFR-alpha and PTEN, were H3K27me3-positive, and had undetectable levels of p53. Sequencing revealed an activating mutation in PI3-kinase (H1047L) and variants of unknown significance in GRK4, FLG, BAZ2A, and CRTC3 . DNA methylation array of the PDX demonstrated 1p loss, which is not typically associated with primary DMG, and broad deletion within 9p including CDKN2A/B, MTAP and multiple interferon genes. The methylation profile did not significantly classify with other tumours in the Molecular Neuropathology database (molecularneuropathology.org/mnp). We describe the first reported PDX model of radiation-associated DMG following medulloblastoma, which recapitulates the patient disease and is molecularly distinct from primary DMG. Interrogation of this model through RNA and whole genome sequencing presents a valuable opportunity to better understand and identify novel therapeutic vulnerabilities against this currently incurable disease.